2020
DOI: 10.1155/2020/6138039
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Immunoinhibitors Identifies LGALS9 and TGFBR1 as Potential Prognostic Biomarkers for Pancreatic Cancer

Abstract: Pancreatic cancer (PC) is one of the most deadly cancers worldwide. To uncover the unknown novel biomarker used to indicate early diagnosis and prognosis in the molecular therapeutic field of PC is extremely of importance. Accumulative evidences indicated that aberrant expression or activation of immunoinhibitors is a common phenomenon in malignances, and significant associations have been noted between immunoinhibitors and tumorigenesis or progression in a wide range of cancers. However, the expression patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
(48 reference statements)
1
11
0
Order By: Relevance
“…TGFB1, mainly secreted by TAMs and CAFs in TME, play an irreplaceable role in inducing immunosuppressive microenvironment. Immunosuppressive genes, such as IL10, IL10RB, LGALS9, and LAG3, were observed to be co-overexpressed with TGFB1 in tumor tissues and predicted poor survival of tumor patients, indicating a potential mechanism by which CCDC137 regulates macrophage polarization, CAFs formation and correlates with several immunosuppressive genes ( Kadowaki et al, 2016 ; Fan et al, 2020 ; Suzuki et al, 2021 ; Wang et al, 2021 ). In addition, the high expression of CCDC137 indicates the immunosuppression status in LGG and UVM, providing a potential drug target for tumor therapy.…”
Section: Discussionmentioning
confidence: 99%
“…TGFB1, mainly secreted by TAMs and CAFs in TME, play an irreplaceable role in inducing immunosuppressive microenvironment. Immunosuppressive genes, such as IL10, IL10RB, LGALS9, and LAG3, were observed to be co-overexpressed with TGFB1 in tumor tissues and predicted poor survival of tumor patients, indicating a potential mechanism by which CCDC137 regulates macrophage polarization, CAFs formation and correlates with several immunosuppressive genes ( Kadowaki et al, 2016 ; Fan et al, 2020 ; Suzuki et al, 2021 ; Wang et al, 2021 ). In addition, the high expression of CCDC137 indicates the immunosuppression status in LGG and UVM, providing a potential drug target for tumor therapy.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Another study suggested LGALS9 and TGFBR1 as novel biomarkers for the prognosis of pancreatic cancer. 25 Li et al found that ICOSLG act as prognostic biomarker in esophageal squamous cell carcinoma associated with an unfavorable overall survival. 26 In colorectal cancer, CD274 was suggested as prognosis biomarker and it could predict the response to anti-PD-1 therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple inflammatory pathways such as tumor necrosis factor-alpha (TNF-α), interferon-gamma (IFN-γ) and nuclear factor-kappa B (NF-κB) are known to induce PD-L1 [50]. Another immune checkpoint marker, LGALS9, was reported to be involved in regulating many of these inflammatory pathways [51]. Thus, we conducted a correlation analysis to elucidate the connection between CD274 (PD-L1 gene) and immune checkpoint markers used earlier (CD47, CD276, CTLA4, HAVCR2, LAG3, LGALS9 and PDCD1).…”
Section: Resultsmentioning
confidence: 99%